Conformational coupling in BK potassium channels - Horrigan, Frank T. (The Rockefeller University Press, 2012)
Large conductance calcium- and voltage-dependent BK potassium channels (aka BK(Ca), MaxiK, Slo1, KCa1.1, and KCNMA1) are expressed in a wide variety of tissues throughout the body and are activated by both intracellular Ca(2+) and membrane depolarization. Owing to these properties, BK channels participate in diverse physiological processes from electrical excitability in neurons and secretory cells, and regulation of smooth muscle tone to tuning of auditory hair cells (Vergara et al., 1998; Ghatta et al., 2006). The response to voltage and Ca(2+) allows BK channels to integrate electrical and calcium signaling, which is central to their physiological role. Understanding how BK and other multimodal channels are regulated by and integrate diverse stimuli is not only physiologically important but also relevant to the topic of conformational coupling. As a voltage- and ligand-dependent channel, BK channels contain both voltage-sensor and ligand-binding domains as well as a gate to regulate the flow of K(+) through the pore. Coupling of conformational changes in one domain to another provides the basis for transducing voltage and ligand binding into channel opening and, therefore, defines, together with the functional properties of the gate and sensors, the signal transduction properties of the channel. The goal of this perspective is to provide an overview on the role and molecular basis of conformational coupling between functional domains in BK channels and outline some of the questions that remain to be answered.